Improved Nutrition through Agricultural Extension and Advisory Services : Case Studies of Curriculum Review and Operational Lessons from India - Babu, Suresh Chandra; Singh, Meera; Hymavathi, T. V.; Rani, K. Uma; Kavitha, G. G.; Karthik, Shree (World Bank, Washington, DC, 2016)
Even after several decades of green revolution, malnutrition continues to be a major development challenge in much of South Asia, and India has a major share of the malnourished people in the region. For nutrition goals to be integrated into extension the curricula provided to current and future agricultural extension agents must be revisited. As part of the South Asia Food and Nutrition Security Initiative (SAFANSI), this paper focuses on approaches to incorporating such nutrition content into the agricultural extension curriculum. Three state agricultural universities in Tamil Nadu, united Andhra Pradesh, and Bihar were used as case studies for the curriculum review. Through these case studies, face-to-face consultations at the national level down to program implementation at the village level have been developed. These include consultative workshops, and a conceptual framework and strategy for incorporating nutrition into extension curriculum development to improve nutrition outcomes. This strategy, detailed in this report, includes opportunities for collaboration from the national level to the community level. Specific lessons and follow-up actions are outlined that may be useful for other South Asian countries. The paper is organized as follows: chapter one gives introduction. Chapter two reviews current literature on agriculture-nutrition linkages to develop a conceptual framework for integrating nutrition into agricultural extension programs. Research methods and approaches are given in chapter three. Results and discussions are given in chapter four. Lessons from the case studies are presented in chapter five, and chapter six consists of concluding remarks.